2013
DOI: 10.1002/j.0022-0337.2013.77.9.tb05593.x
|View full text |Cite
|
Sign up to set email alerts
|

Thai Dental Practitioners’ Knowledge and Attitudes Regarding Patients with HIV

Abstract: To investigate the knowledge and attitudes of Thai dental practitioners regarding patients with HIV, a cross-sectional study using self-administered questionnaires was conducted. The questionnaires requested demographic information and included questions evaluating the knowledge and attitude of dental practitioners towards HIV. The results were analyzed using Scheffe method for multiple comparisons at the 95 percent conidence level. Out of 1,200 questionnaires sent, 446 questionnaires were returned (response r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
(40 reference statements)
0
10
0
1
Order By: Relevance
“…This failure to inform their dentist could be due to several factors. Fear of refusal of dental treatment or fear of stigmatization are probably the most common reasons for not disclosing HIV infection 20 . Indeed, dentists' concerns regarding increased personal risk is the most frequently reported reason for their reluctance to treat HIV-infected patients 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This failure to inform their dentist could be due to several factors. Fear of refusal of dental treatment or fear of stigmatization are probably the most common reasons for not disclosing HIV infection 20 . Indeed, dentists' concerns regarding increased personal risk is the most frequently reported reason for their reluctance to treat HIV-infected patients 39 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a study in India among 130 HIV infected patients, a prevalence of periodontitis of 20% was found 15 while a very small study (n=29) in Brazil reported a prevalence of 86% 16 . This variation can be explained by the different definitions used in the studies 17,18 , differences in social and economic status 19 as well as the availability of dental care and oral care awareness and the attitudes of dental practitioners 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Human Immunodeficiency Virus (HIV) is a virus that was discovered by a French virologist and joint recipient, Luc Antoine Montagnier with Francoise Barre-Sinoussi and Harald zur Hausen. It came to light first when rare opportunistic infections and treatment resistant cancers began to develop among number of healthy homosexual males in New York [1]. HIV virus is a virus that attacks the immune system of body's natural defence mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge and attitude of dental practitioners towards HIV has been studied in several countries and revealed surprising results. Dental practitioners have been found to have discriminatory attitudes that potentially affect dental treatment for patients with HIV (21).…”
Section: Discussionmentioning
confidence: 99%